Yucca Giant-Skipper Butterfly, Megathymus yuccae (Boisduval & Leconte) (Insecta: Lepidoptera: Hesperiidae) - Jaret C. Daniels (EDIS, 2009)
EENY-427, a 3-page illustrated fact sheet by Jaret C. Daniels, is part of the Featured Creatures collection. It describes this large and robust-bodied butterfly found in habitats supporting yucca — distribution, description, life cycle, and hosts. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.